Se gli inumani siamo noi. Riflessioni sulla narrazione intergenerazionale dei crimini di guerra commessi dal gruppo di appartenenza - Giovanna Leone (Rivista Internazionale di Filosofia e Psicologia, 2011)
When we are the Inhumane. Reflections on Intergenerational Narratives of War Crimes Committed by the Ingroup - This article focuses on factors that may facilitate intergroup reconciliation. In this frame, intergenerational narratives intended for descendants of a group charged with war crimes are considered in depth. Although heavy burdens, these narratives are necessary to avoid false reconciliations. Intergroup reconciliation requires, in fact, that several generations elaborate a symbolic loss, which forms a part of their in-group identity. For descendents of the group that is more responsible for war violence, this identity loss relates to the human dignity of their group. Results of empirical research, in which 103 Italian university students read a narrative describing overtly (vs. evasive) war crimes enacted by the Italian Army during the invasion of Ethiopia (1935-36), suggest that explicit narratives of inhuman acts committed by one’s own group may facilitate this kind of reconciliation.